ORIENTAÇÕES SOBRE A COLETA DE MATERIAL BIOLÓGICO PARA REALIZAÇÃO DE EXAMES LABORATORIAIS - Chaves, Hiandra S.; Schneider, Aline; Ott, Joice N.; Oliveira, Karla R. D.; Palmeira, Daniel D. (Salão do Conhecimento, 2013)
Resumo